2013
DOI: 10.1109/lcomm.2013.071013.131029
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Jump-Stay Rendezvous Algorithm for Cognitive Radio Networks

Abstract: Rendezvous is a fundamental operation for cognitive users to establish communication links. In [5], we proposed a jump-stay (JS) rendezvous algorithm which was shown to have the overall best performance. In this work, we propose an enhanced jump-stay (EJS) algorithm. Compared with JS, EJS lowers the upper-bounds of both the maximum timeto-rendezvous (MTTR) and the expected time-to-rendezvous (E(TTR)) from O(P 3 ) to O(P 2 ) under the asymmetric model, while keeping the same order O(P ) of upper-bounds of MTTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 6 publications
1
74
0
2
Order By: Relevance
“…In each period, JS continuously switches channels during the jump pattern (2P time slots) and then stays on a specific channel during the stay pattern (P time slots). The EJS algorithm [16] is modified from JS, in which the jump pattern is prolonged to 3P time slots. EJS achieves shorter MTTR/ETTR than JS when SUs own asymmetric channels.…”
Section: A Pairwise Single-radio Rendezvous Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each period, JS continuously switches channels during the jump pattern (2P time slots) and then stays on a specific channel during the stay pattern (P time slots). The EJS algorithm [16] is modified from JS, in which the jump pattern is prolonged to 3P time slots. EJS achieves shorter MTTR/ETTR than JS when SUs own asymmetric channels.…”
Section: A Pairwise Single-radio Rendezvous Algorithmsmentioning
confidence: 99%
“…It can be observed that the MTTR of MSS is shorter than RPS under all values of G. However, MSS does not outperform Mc-Broadcast when G 15. Only when G increases to [16,20] can MSS outperform Mc-Broadcast. Even so, Mc-Broadcast is not quite a flexible algorithm.…”
Section: B Pairwise Multiradio Scenariomentioning
confidence: 99%
“…In this paper, we consider that during the rendezvous attempt the PUs operate in a fixed set of channels and that the SUs have prior knowledge of the state of each of the network channels a . With this knowledge, some authors [16,[25][26][27][28][29] provide each SU with the ability to attempt to rendezvous only in a channel previously identified as available (free of PU interference).…”
Section: Related Workmentioning
confidence: 99%
“…Most works regarding CH rendezvous [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] consider that the time is divided into slots and the time to rendezvous (TTR) is defined as the number of time slots needed to successfully rendezvous after all SUs have begun the CH sequences. Moreover, the expected TTR (ETTR) and the maximum TTR (MTTR) are two important metrics commonly used to evaluate these strategies and are often computed when all channels are available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation